Pendidikan agama Islam mengurangi agresivitas santri di pesantren sebagai bagian anak bangsa - Maulani, Kharisma (Maliki Interdisciplinary Journal, 2024)
Juvenile fights are an example of this act of violence. Verbal aggression, such as taunting, sarcasm, and offensive language, is what usually precedes physical aggression. Many people strongly believe that pesantren are a very smart alternative approach for adolescents to avoid the unfavorable influence of global development. However, it does not completely eliminate the possibility, because aggressive attitudes are also crowded among students. The purpose of this article is to determine the effectiveness of religious education programs in reducing aggressiveness among students. The method used in this article is the article review approach. The results obtained in this article are that many factors cause aggressive attitudes among students. Like a teacher hitting his classmates who were witnessed by other students so that they think violence is permissible. In addition, internal factors in the family are also the trigger. The thing that encourages young students to be able to reduce this aggressiveness is a strong understanding of religion and apply it in everyday life. This is the importance of religious education in reducing the level of violence among adolescents, especially students.